Association between ultra-processed food consumption and gut microbiota in senior subjects with overweight/obesity and metabolic syndrome - Atzeni, Alessandro; Martínez, María Ágeles; Babio, Nancy; Konstanti, Prokopis; Tinahones, Francisco J.; Vioque, Jesús; Corella, Dolores; Fitó, Montserrat; Vidal, Josep; Moreno-Indias, Isabel; Pertusa-Martinez, Salvador; Álvarez-Sala, Andrea; et al. (Frontiers in Nutrition, 2022)
The production and consumption of ultra-processed foods (UPF) has increased considerably during the last years worldwide. Collective evidence shows the association between UPF consumption and adverse health outcomes, including inflammatory gastro-intestinal disorders and obesity. The gut microbiota has been suggested as potential mediator of the effects of UPF consumption on metabolism and health. However, few studies have been conducted in order to elucidate these aspects. Therefore, the aim of the present study was to assess the cross-sectional associations between UPF consumption and gut microbiota in a population of senior subjects (n=645) within the frame of the PREDIMED-Plus trial. Eligible participants were men and women (aged 55–75 years), without documented history of cardiovascular disease at enrollment, with overweight/obesity (body mass index ≤ 27 and <40 kg/m2) and metabolic syndrome. Using the information of food frequency questionnaires, the consumption of UPF, expressed as a percentage of total dietary energy intake in kcal/day, was calculated considering those food items classified in group 4 of NOVA system. Population was categorized according to tertiles of UPF consumption. Taxonomic fecal microbiota information, along with blood biochemical parameters, anthropometric measurements and clinical data were obtained. Bioinformatics analysis was performed to study the association between fecal microbiota composition and UPF consumption. We observed that subjects allocated in the highest tertile of UPF consumption (21.4 ± 5.0 % kcal/day) presented lower adherence to MedDiet (p<0.001) and higher total energy intake (p<0.001). The taxonomic analysis of the fecal microbiota revealed a significant (Benjamini-Hochberg adjusted p<0.2) positive association between specific taxa and tertiles (T) of UPF consumption: Alloprevotella (p=0.041 vs T2; p=0.065 vs T3), Negativibacillus (p=0.096 vs T3), Prevotella (p=0.116 vs T3), and Sutterella (p=0.116 vs T2). UPF consumption was positively associated with lower adherence to MedDiet and higher total energy intake in senior subjects with overweight obesity and metabolic syndrome. In addition, positive association with specific fecal microbiota taxa related to inflammatory gastro-intestinal diseases and low consumption of fruits and vegetables, was observed.